2020
DOI: 10.3390/medicina56010034
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 23-Producing Phosphaturic Mesenchymal Tumor with Extraordinary Morphology Causing Oncogenic Osteomalacia

Abstract: A possible cause of hypophosphatemia is paraneoplastic secretion of fibroblast growth factor 23 (FGF-23). Tumors secreting FGF-23 are rare, mostly of mesenchymal origin, usually benign, and may be located anywhere in the body, including hands and feet, which are often not represented in conventional imaging. A 50-year-old woman presented with diffuse musculoskeletal pain and several fractures. Secondary causes of osteoporosis were excluded. Laboratory analysis revealed hypophosphatemia and elevated alkaline ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Small studies by Agrawal et al [ 46 ] and Jadhav et al [ 47 ] also reported higher sensitivity and specificity for SSTR tracers compared with [ 18 F]FDG. Multiple other case and small studies summarized in Table 2 report localization of culprit lesions in patients with TIO using SSTR tracers [ 14 , 38 , 39 , 40 , 41 , 42 , 44 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. An example showing culprit lesions identified in 3 patients using [ 68 Ga]Ga-DOTATATE PET-CT from a small study by John et al [ 38 ] is shown in Figure 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Small studies by Agrawal et al [ 46 ] and Jadhav et al [ 47 ] also reported higher sensitivity and specificity for SSTR tracers compared with [ 18 F]FDG. Multiple other case and small studies summarized in Table 2 report localization of culprit lesions in patients with TIO using SSTR tracers [ 14 , 38 , 39 , 40 , 41 , 42 , 44 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. An example showing culprit lesions identified in 3 patients using [ 68 Ga]Ga-DOTATATE PET-CT from a small study by John et al [ 38 ] is shown in Figure 5 .…”
Section: Discussionmentioning
confidence: 99%
“…On MRI, HFLT presents as a soft tissue mass with indistinct margins, intralesional fat, and septations with local recurrence and occasionally blood products on GRE [ 32 ]. PMT, which is classified as a rarely metastasising lesion, is an extremely rare but clinically and histologically distinctive tumour that produces fibroblast growth factor 23, a hormone that blocks the reuptake of phosphate by proximal renal tubule, resulting in phosphaturia [ 33 ]. As such, PMTs produce phosphaturia and result in tumour-induced osteomalacia, which resolves with complete PMT excision [ 34 ].…”
Section: Tumours Of Uncertain Differentiationmentioning
confidence: 99%
“…As such, PMTs produce phosphaturia and result in tumour-induced osteomalacia, which resolves with complete PMT excision [ 34 ]. Clinically, the majority of patients with PMT exhibit elevated serum levels of fibroblast growth factor 23 [ 33 ]. PMTs tend to have a non-specific imaging appearance and can mimic TSGCT, and even ALT [ 35 ].…”
Section: Tumours Of Uncertain Differentiationmentioning
confidence: 99%